1999
DOI: 10.21273/jashs.124.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Source and Timing of Calcium and Nitrogen Applications on `Atlantic' Potato Tuber Calcium Concentrations and Internal Quality

Abstract: Three Ca sources and two application schedules were compared for their effectiveness for increasing tissue Ca concentrations in 170 to 284 g field-grown tubers of `Atlantic' potato (Solanum tuberosum L.). Additional observations were made of internal physiological defects. Paired measures of tissue (periderm and nonperiderm) Ca concentration and internal quality (±hollow heart, ±internal brown spot) were made on individual tubers produced in plots fertilized with N at 224 kg·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
8
24
0
Order By: Relevance
“…This increase in tuber Ca concentration varied among cultivars and among seasons at both locations but appears to have no relationship with soil Ca. Our recent studies have shown that in-season application of Ca can increase tuber Ca concentration and improve tuber quality (Palta 1996;Kleinhenz et al 1999;Ozgen et al 2006;Karlsson et al 2006). Frequently asked questions include: when should supplemental Ca be applied and at what soil test Ca level should these applications be made to provide adequate Ca for tuber quality?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase in tuber Ca concentration varied among cultivars and among seasons at both locations but appears to have no relationship with soil Ca. Our recent studies have shown that in-season application of Ca can increase tuber Ca concentration and improve tuber quality (Palta 1996;Kleinhenz et al 1999;Ozgen et al 2006;Karlsson et al 2006). Frequently asked questions include: when should supplemental Ca be applied and at what soil test Ca level should these applications be made to provide adequate Ca for tuber quality?…”
Section: Resultsmentioning
confidence: 99%
“…The soils in these two areas are loamy sand and silt loam, respectively, and the soil at our experimental sites tested at 285 to 563 and 530 to 1,340 mg kg −1 of exchangeable Ca, respectively. In spite of these high soil test values, we have been able to increase the tuber Ca concentration and reduce tuber internal defects as well as reduce black spot bruising by in-season application of 168 kg ha −1 Ca during the tuber bulking period (Kleinhenz et al 1999;Ozgen et al 2006;Karlsson et al 2006). The objective of the present study was to determine the relationship between exchangeable soil Ca and tuber Ca, with and without in-season Ca fertilization.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is evident from the published data that the mineral composition of potato tubers plays an important role in the tuber's overall health including protection against numerous potato-related diseases (Kleinhenz et al 1999;Mondy and Ponnampalam 1986;Bretzloff 1971;Lambert et al 2005;Davies 1998). Conversely, diseases can influence greatly the mineral composition of potatoes ultimately leading to diminished tuber nutrition and crop loss (Chandra and Mondy 1981;Krištůfek et al 2000;Hoveland et al 1954;Ulrychová and Limberk 1968).…”
Section: Discussionmentioning
confidence: 99%